L''Ovidius moralizatus' de Pierre Bersuire. Essai de mise au point - Marek Thue Kretschmer (Interfaces: A Journal of Medieval European Literatures, 2017)
Thanks to the age-long efforts of Birger Munk Olsen, to whom the present article is dedicated, we have a good overview of how the Roman classics were spread, read, and (re-)used up to the year 1200, but we have no such cicerone for the Late Middle Ages. Taking the medieval commentaries on the Metamorphoses as a point of departure, the article is an attempt to open up the Ovidius moralizatus of Pierre Bersuire, a fourteenth-century commentary that hitherto has received relatively little notice due to the lack of a critical edition. After a preliminary discussion of how the Ovidius moralizatus relates to the earlier medieval commentary tradition and a general assessment of the Avignon and Paris versions, the core of the article focuses on the explanatory principles.